Experimental Insights and Recommendations for Successfully Performing Cerebral Microdialysis With Hydrophobic Drug Candidates - Julia K. Sundheimer; Julia Benzel; Rémi Longuespée; Jürgen Burhenne; Stefan M. Pfister; Kendra K. Maaß; Max Sauter; Kristian W. Pajtler (Clinical and Translational Science)
ABSTRACT Cerebral microdialysis in rodents represents a robust and versatile technique for quantifying the pharmacologically relevant unbound fraction of drugs in the brain. When this unbound fraction is simultaneously determined in plasma, it facilitates the calculation of the corresponding unbound plasma‐to‐brain partition coefficient (Kp,uu) for a given compound in vivo. This coefficient is critical for understanding the penetration and distribution of drugs across the blood–brain barrier (BBB). However, obtaining valid and accurate microdialysis data can be particularly challenging for hydrophobic drugs due to their pronounced non‐specific interactions with the components of the microdialysis system. The present study reports the outcomes of comprehensive microdialysis investigations in rodents, focusing on three hydrophobic compounds: actinomycin D, selinexor, and ulixertinib. These compounds exhibited varying degrees of non‐specific binding to the surfaces of the microdialysis apparatus, leading to low recovery rates and substantial carry‐over effects. To diminish these limitations, strategies such as surface coating and the use of optimized materials were employed to enhance the reliability of the microdialysis system. To ensure the robustness and reproducibility of microdialysis‐related research outcomes, our experimental findings were supplemented with a narrative literature review. This review encompassed keyword‐driven PubMed‐indexed publications on microdialysis from 1970 to 2024, providing a broader context for the challenges and solutions associated with the technique. By integrating empirical results with practical recommendations, this study offers a comprehensive resource aimed at advancing the application of cerebral microdialysis in preclinical drug development, particularly for compounds with challenging physicochemical properties.